1994
DOI: 10.1212/wnl.44.5.815
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac injury associated with neurogenic pulmonary edema following subarachnoid hemorrhage

Abstract: A reversible form of cardiac injury may occur in patients with NPE following SAH and is associated with characteristic clinical findings. Impaired LV hemodynamic performance in this setting may contribute to cardiovascular instability, pulmonary edema formation, and complications from cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 0 publications
5
118
0
5
Order By: Relevance
“…Pulmonary edema worsens the prognosis of SAH and increases the mortality rate. 20 Therefore, preventing the development of pulmonary edema in patients with SAH is of utmost importance. In our study, the incidence of pulmonary edema in patients with SAH was 25%, and the rate was higher in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary edema worsens the prognosis of SAH and increases the mortality rate. 20 Therefore, preventing the development of pulmonary edema in patients with SAH is of utmost importance. In our study, the incidence of pulmonary edema in patients with SAH was 25%, and the rate was higher in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…16) Although these two complications had been regarded as separate entities in the past, 18,35) recent studies indicate that they share a common pathophysiology and may coexist in the same patient. 12,20,21,24,31) The common pathophysiology involves massive catecholamine release, particularly norepinephrine, into the circulation immediately after aneurysm rupture, and is responsible for endothelial damage, vasoconstriction, and increased vascular permeability. 7,20,21) However, how often SAH patients complicated with NPE also have concomitant TCM (NPE-TCM) remains unclear, since evaluation of cardiac wall motion using transthorac-…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the majority of patients sustained poor-grade (grade IV or V) SAH, whereas previous studies had smaller percentages of poor-grade SAH patients. 3,24) We made every effort to obtain CT angiography, and finally investigated 100% of grade IV and 84% of grade V patients. This study found a higher incidence of ECG abnormality (Table 1) compared with previous reports, in which ST segment change and QTc prolongation was observed in 46% and 31%, 21) but may be explained by the difference in disease severity.…”
mentioning
confidence: 99%
“…9) Such cases tend to be severe, and are often associated with pulmonary lung edema and hemodynamic instability. 10,12) Some cases may be ampulla (takotsubo) cardiomyopathy. The prognosis is usually good, but our case suggests that careful management of water balance and heart function is necessary.…”
Section: Discussionmentioning
confidence: 99%